Penggunaan blog-gothic pada mata kuliah geometri analitik - Rohmah Indahwati; Chairul Fajar Tafrilyanto (Math Didactic: Jurnal Pendidikan Matematika, 2018)
One of the four competencies that teachers and lecturers must possess is professional competence. A lecturer must be able to master and develop material in accordance with the field of science that is taught and can take advantage of advances in technology, information, and communication (ICT) as a communication medium that supports teaching and learning activities. Similarly for students who have the ability to ask questions and argue differently. Students only give a little bit solution to the problem given due to the lack of media to express themselves in asking freely without feeling embarrassed and the limitations of face-to-face hours. Blog media as one of the learning media through the internet or media interaction between students and lecturers. The use of this media as an alternative in overcoming the limitations of face-to-face hours during lectures and of course utilizing the progress of information and communication technology that is developing at this time. The blog in question is given the name of a gothic blog as a learning center which includes lecture plans, teaching materials, assignments of reference links, videos and discussion material on the subject of analytical geometry. In addition, there are lecturer and student blogs to interact with each other. There is also a community of learning bloggers that allows interaction and communication between lecturers and students as well as from various universities to join the blogger learning community.